2008
DOI: 10.1159/000113507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasmapheresis on the Immune System in Endotoxin-Induced Sepsis

Abstract: Background: It has been proposed that plasmapheresis is most effective when applied early in Gram-negative sepsis. We therefore studied the effect of early plasmapheresis on immunity in experimental Escherichia coli endotoxin-induced sepsis. Methods: 20 pigs received 30 µg/kg of E. coli endotoxin. 40 min later, half of the pigs were treated with plasmapheresis which lasted 4 h. The adhesion molecules, the oxidative burst, the number of neutrophils in blood and lungs, and cytokines were measured. Results: Infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…After the treatment, symptoms of sepsis (fever, leukocytosis, and unstable hemodynamic status) and liver dysfunction (increase of bilirubin and transaminase levels) were all relieved significantly ( fig. 2 ) just as reported by other authors [14,16] . The patient's vital signs stabilized immediately after 3 times of hemoperfusion and plasmapheresis.…”
Section: Discussionsupporting
confidence: 80%
“…After the treatment, symptoms of sepsis (fever, leukocytosis, and unstable hemodynamic status) and liver dysfunction (increase of bilirubin and transaminase levels) were all relieved significantly ( fig. 2 ) just as reported by other authors [14,16] . The patient's vital signs stabilized immediately after 3 times of hemoperfusion and plasmapheresis.…”
Section: Discussionsupporting
confidence: 80%
“…Only very limited data are available in the medical literature regarding plasmapheresis, plasma exchanges, and related techniques for this indication [51-55]. Nevertheless, it has been suggested that these therapies might be beneficial, especially for patients with Gram-negative sepsis [52,54,56,57] and when implemented as early as possible [58].…”
Section: Plasmapheresis and Coupled Plasma Filtration Adsorptionmentioning
confidence: 99%
“…New blood purification techniques, such as high-volume hemofiltration, coupled-apheresis and adsorption, large-pore HF or HD, might modulate immune system to some extent, but a lot of controversies exist on this point. So the clinical value of these techniques remains further research [16,17] . Recent research has pointed to the pivotal role that ECs plays in severe sepsis.…”
Section: Discussionmentioning
confidence: 99%